The Effects of Exercise Intensity and Duration on Excess Post-Exercise Oxygen Consumption - Sloman, Heather (My University, 1990)
The effects of exercise intensity and duration on excess post-exercise oxygen consumption (EPOC) were examined. Eight males exercised in a thermoneutral environment at 60% of maximal aerobic power (V0₂ₘₐₓ) for 30 min and performed the same total work at 80% and 40% V0₂ₘₐₓ by varying exercise durations. In addition, 2 work bouts were performed at 60% VO₂ₘₐₓ for 90 and 60 min. A standardized meal was consumed 2 h post-exercise. Oxygen consumption (V0₂), respiratory exchange ratio (RER), rectal temperature (Tc) and heart rate (HR) were monitored on a control day and before, during and for 3 h following exercise. VO₂ was equivalent to control day values within 30 min post-exercise on each of the 5 d and no consistent relation between exercise condition and duration of EPOC was observed. When total post-exercise VO₂ was expressed relative to control values, differences were greatest during the first 30 min post-exercise. Total net caloric expenditure was small (32. 5-57.9 kcal) in all cases. RER tended to remain equivalent to control levels post-exercise, with intermittent elevations. Significant elevations in Tc were obtained until 60 to 150 min post-exercise. No significant exercise-related effects were noted for dietary induced thermogenesis or the cumulative effect of the 5 exercise bouts on resting metabolic rate. Although exercise over a wide range of intensities and durations resulted in a significant EPOC, in all cases it was of short duration and the total 3 h energy expenditure was small. Neither duration nor magnitude of EPOC was associated with post-exercise RER or Tc.
Keywords: exercise intensity; oxygen; post-exercise